Improved modularity-based approach for partition of Water Distribution Networks. Issue 2 (7th February 2021) - Yao, Huaqi; Zhang, Tuqiao; Shao, Yu; Yu, Tingchao; Lima Neto, Iran E.
ABSTRACT: The partition of complex Water Distribution Systems (WDSs) is required in order to simplify and facilitate the routine cumbersome management tasks. As a representative community detection algorithm, the Fast-Newman Algorithm (FNA) can efficiently partition the network into District Metered areas (DMAs) based on the modularity index. However, only the topological attribute is considered in the classic version. In this work, the modularity index and corresponding mergence mechanism of FNA are modified first to improve water demand similarity among DMAs; then, an optimal selection of cut positions where flow meters or gate valves will be installed is conducted to further improve water demand similarity among DMAs; finally, the inflow pipes of DMAs are optimally selected considering economy and the impact on hydraulic performance of WDSs. The proposed approach is applied to three cases and the results reveal the superiority of this method.